Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Statistical Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
This report reviews developments in the implementation of the Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI). It also provides updates on debt service and poverty-reducing expenditure by beneficiary countries, as well as on the cost of debt relief, creditor participation rates, and litigation against HIPCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet